Acute pancreatitis. Issue 6 (June 2016) - Thomasset, Sarah C.; Carter, C Ross
Abstract: Acute pancreatitis is a common diagnosis and its incidence may be rising. The most common aetiological agents remain gallstones and alcohol misuse. Eighty per cent of patients will have a mild attack which resolves within a few days without specific treatment. Severe disease is characterized by a significant systemic inflammatory response which may be associated with varying degrees of organ dysfunction. The mortality in patients with multi-organ failure may be as high as 50%. This article reviews the definition, aetiology, pathophysiology, therapeutic strategies and outcomes in light of recent evidence.